Self Management Berhubungan Dengan Nilai Tekanan Darah Pada Pasien Hipertensi - Ambarwati, Hevy; Rosyid, Fahrun Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine whether there is a relationship between self-management and blood pressure values ​​in hypertensive patients at UNS Hospital. The method used in this research is a cross sectional approach with a correlational quantitative descriptive research design. The research results were based on the results of the Spearman rank correlation test between self-management and blood pressure values, with a p-value of 0.000 and a correlation coefficient value of 0.363. The results of the research show that there is a correlation between self-management and blood pressure values ​​in hypertensive patients with the level of strength of the relationship between the two variables in the sufficient category. In conclusion, there is a relationship between self-management and blood pressure values ​​in hypertensive patients. Keywords: Self Management, Blood Pressure, Hypertension